Digital Literacy Education in Maine’s Public Libraries - Conners, Michelle (Maine Policy Review, 2024)
In today’s rapidly advancing technological environment, digital literacy skills are crucial for active engagement in society. Maine’s public libraries have initiated efforts to provide digital literacy education to their communities. However, these endeavors face challenges due to inadequate resources. This study investigates how Maine’s public libraries tackle digital literacy education, the required resources, and the associated opportunities and challenges. The findings highlight the urgent need for federal and state support to adequately fund digital literacy education as existing funding and staffing models struggle to meet community demands. Additionally, as digital literacy becomes indispensable for accessing essential services like medical appointments and government documents, addressing the gap between access and knowledge requires comprehensive educational initiatives.